Pengaruh Debt to Equity Ratio, Return On Asset dan Return On Equity Terhadap Return Saham (Studi Kasus pada Perusahaan Sub Sektor Perbankan yang Tercatat di Bursa Efek Indonesia Periode 2016-2021) - Sueno, Risky Chandra (SWOT : Jurnal Ilmiah Ilmu Manajemen, 2026)
This study aims to determine and analyze the effect of Debt to Euity Ratio, Return On Equity, and Return On to Stock Return (Case Study on Banking Sub-Sector Companies Listed on The Indonesia Stock Exchange 2016 - 2021). The population that will be used in this study are all banking sub-sector companies listed on the Indonesia Stock Exchange for the 2016-2021 period, namely 5 populations. The sample that will be used in this study is 5 samples of banking sub-sector companies listed on the Indonesia Stock Exchange for the 2016-2020 period. The sample selection method in this study uses a saturated sample technique, which is a sample determination technique if all members of the population are used as samples. The data collection method uses a literature study technique with secondary data types, namely data that has been processed or presented and has been published on the IDX website. The data processing method in this study uses panel data regression analysis with the help of EViews version 10 software. The results of this study indicate that the Debt to Equity Ratio has no effect on stock returns and Return on Assets and Return on Equity have a positive and significant effect on stock returns.